Effect of Artificial Ageing on Adhesive Bonds from Heat Treated Spruce - Mirko Kariz (University of Zagreb, Faculty of Forestry and Wood Technology, 2021)
The influence of artificial ageing on bonded heat-treated spruce lamellas was investigated. Heat-treated spruce lamellas with different degrees of thermal modification were bonded with PVAc and MUF and then exposed to 500 artificial weathering cycles, combined with rain, UV and IR radiation. The colour change of the exposed surface, weight change, delamination of the bonded joints and adhesive bond strength were measured. Artificial weathering caused cracking and delamination of the bonded joints and reduced the bond strength of both adhesives. The results show that delamination was higher for PVAc adhesive than MUF, but increased for both adhesives with the temperature of heat treatment of wood. The shear strength of bonds on the exposed side of the samples after the artificial weathering was lower than the average strength of the whole sample.